Freemason anticlericalism in Brazil in the second half of the 19th century: the debate between the “impious press” and the Catholic press - Cloclet da Silva, Ana Rosa (2024)
This article seeks to explore some nuances of Freemason anti-clericalism in Brazil in the second half of the 19th century, focusing on the period of the Religious Question (1872-1875). To this end, it takes as its object of study the discursive formulations present in two of the main Freemason newspapers then published in Brazil: the Boletim do Grande Oriente do Brazil (1871-1899) and the Boletim do Grande Oriente Unido e Supremo Conselho do Brazil (1873-1877). From a methodological point of view, it is supported by two main references: Discourse Analysis and the History of Concepts, aiming at a historical-semantic approach.